The use of lifting straps during snatch alters muscle activation patterns - Lemus, S. A.; Volz, M.; Chen, C.-B.; Mann, B. J.; Travascio, F. (International Journal of Sports Science & Coaching, 2025)
The snatch is prevalent in competitive and recreational lifting as well as strength training. Lifting straps (LS) are an accessory that wrap around the hand and the barbell, reducing the limitations of grip strength. However, this benefit has not been quantitatively supported for the snatch. The aim of this study was to compare muscle activation patterns between using LS and not using them at 80% of the snatch one-repetition maximum in a group of twelve sub-elite male weightlifters. It was hypothesized that LS would decrease forearm muscle activation and increase larger muscle group activation. Eight dominant-side muscles located in the lower limbs, back, shoulders, and upper limbs were measured via electromyography. A two-way analysis of variance (ANOVA), followed by a Tukey Pairwise comparison, revealed that LS significantly impacted (p = 0.039) muscle activation in the snatch. Specifically, latissimus dorsi activation increased the most (17.2 ± 55.7%), while biceps brachii activation decreased the most (-8.0 ± 37.0%). Comparing muscle activation across different phases of the lift showed that LS decreased forearm and bicep brachii activation by 16.0 ± 25.2% and 7.1 ± 35.7% respectively during the pull phase, and increased vastus lateralis, latissimus dorsi, and medial deltoid activation between the second part of the first pull and the catching position, with a corrected effect size exceeding 1.5. These results support the hypothesis that LS decrease forearm activation, which could reduce grip strength limitations and consequently, reduce problems associated with fatigue. Increases in vastus lateralis activation with the use of LS suggest a greater training stimulus during the snatch, which can help develop leg strength.